(untitled) (Scientific journal of the Fergana State University, 2023)
It is known that the Ulan genre has been given various definitions, descriptions and classifications. What do the creators and performers themselves think about this? What is the purpose of their creation? What is the reason that they remain in memory for a long time, and have always been of interest to the audience of listeners? This article attempts to find answers to these questions. In general, the needs of lancers in the work of lancers, the factors of the emergence of lancers, their definitions are discussed and classified. In order to achieve deeper scientific observations and their results, the study studied the method of comparative typological analysis as follows: 1) traditionality; 2) eranian patronage; 3) administrative disobedience; 4) motivational character; 5) financial incentive; 6) spiritual stimulus; 7) compensation for defeat; 8) execution regulations; 9) has been classified as a meditative remedy.